Inference of the protokaryotypes of amniotes and tetrapods and the evolutionary processes of microchromosomes from comparative gene mapping. - Yoshinobu Uno; Chizuko Nishida; Hiroshi Tarui; Satoshi Ishishita; Chiyo Takagi; Osamu Nishimura; Junko Ishijima; Hidetoshi Ota; Ayumi Kosaka; Kazumi Matsubara; Yasunori Murakami; Shigeru Kuratani; et al. (PLoS ONE, 2012)
Comparative genome analysis of non-avian reptiles and amphibians provides important clues about the process of genome evolution in tetrapods. However, there is still only limited information available on the genome structures of these organisms. Consequently, the protokaryotypes of amniotes and tetrapods and the evolutionary processes of microchromosomes in tetrapods remain poorly understood. We constructed chromosome maps of functional genes for the Chinese soft-shelled turtle (Pelodiscus sinensis), the Siamese crocodile (Crocodylus siamensis), and the Western clawed frog (Xenopus tropicalis) and compared them with genome and/or chromosome maps of other tetrapod species (salamander, lizard, snake, chicken, and human). This is the first report on the protokaryotypes of amniotes and tetrapods and the evolutionary processes of microchromosomes inferred from comparative genomic analysis of vertebrates, which cover all major non-avian reptilian taxa (Squamata, Crocodilia, Testudines). The eight largest macrochromosomes of the turtle and chicken were equivalent, and 11 linkage groups had also remained intact in the crocodile. Linkage groups of the chicken macrochromosomes were also highly conserved in X. tropicalis, two squamates, and the salamander, but not in human. Chicken microchromosomal linkages were conserved in the squamates, which have fewer microchromosomes than chicken, and also in Xenopus and the salamander, which both lack microchromosomes; in the latter, the chicken microchromosomal segments have been integrated into macrochromosomes. Our present findings open up the possibility that the ancestral amniotes and tetrapods had at least 10 large genetic linkage groups and many microchromosomes, which corresponded to the chicken macro- and microchromosomes, respectively. The turtle and chicken might retain the microchromosomes of the amniote protokaryotype almost intact. The decrease in number and/or disappearance of microchromosomes by repeated chromosomal fusions probably occurred independently in the amphibian, squamate, crocodilian, and mammalian lineages.